Discourse‐level reading comprehension in Chinese children: what is the role of syntactic awareness?. (9th October 2013) - Tong, Xiuhong; Tong, Xiuli; Shu, Hua; Chan, Shingfong; McBride‐Chang, Catherine; Kendeou, Panayiota
<x xml:space="preserve">Abstract</x> This study aimed to investigate the association between syntactic awareness and discourse‐level reading comprehension in 136 Hong Kong Chinese children. These children, aged 11, from a longitudinal study, were administered a set of cognitive and linguistic measures. Partial correlational analyses showed that children's performances in two syntactic tasks were significantly correlated with their discourse‐level reading comprehension. A multiple hierarchical regression analysis indicated that syntactic skills, especially the conjunction cloze task, accounted for unique variance in reading comprehension even when age, nonverbal IQ, phonological awareness, morphological awareness and vocabulary knowledge, as well as the auto‐regressive effect of previous reading comprehension skill were statistically controlled in this study. Findings suggest that syntactic awareness is uniquely associated with discourse‐level reading comprehension in Hong Kong fifth graders.